Does previous prostate surgery affect multiparametric magnetic resonance imaging accuracy in detecting clinically significant prostate cancer? Results from a single institution series. Issue 12 (10th May 2022) - Pellegrino, Francesco; Stabile, Armando; Mazzone, Elio; Sorce, Gabriele; Barletta, Francesco; De Angelis, Mario; Brembilla, Giorgio; Gandaglia, Giorgio; De Cobelli, Francesco; Montorsi, Francesco; Briganti, Alberto
Abstract: Background: Multiparametric MRI (mpMRI) has demonstrated high diagnostic accuracy for clinically significant PCa (csPCa). However, the accuracy of this test in men that received a previous prostatic surgery is still controversial. We aimed at assessing the effect of previous prostatic surgery on the detection of csPCa in a tertiary referral center. Method: We relied on a cohort of 311 men with a positive mpMRI (prostate imaging ‐ reporting and data system [PI‐RADS] ≥ 3) who underwent a targeted (TBx) plus concomitant systematic random biopsy (SBx) at a single tertiary referral center between 2017 and 2020. The study outcome was to compare the detection of csPCa (Gleason score ≥ 3 + 4) between the two groups (no previous prostate surgery [Group 1] vs. previous prostate surgery [Group 2]). Multivariable logistic regression analysis (MVA) was used to assess the relationship between previous prostate surgery and the detection of csPCa at TBx, after taking into account potential clinical confounders. Results: Overall, 24 (8%) patients received a previous prostate surgery before undergoing mpMRI. Median prostate‐specific antigen density was 0.15 versus 0.08 ng/ml/cc, in Group 1 versus 2, respectively. The most frequent finding at mpMRI was in Group 1 versus 2, PI‐RADS 4 (55%) versus PI‐RADS 3 and 4 (42% each). The majority of patients were biopsy naïve in both Groups 1 (66%) and 2 (71%). The overall detection of csPCa in Group 1 versus 2 was 83% versus 75%, respectively. Differently, the detection of csPCa at TBx in Groups 1 versus 2 was 76% versus 71%, respectively. At MVA, previous prostate surgery (odds ratio: 0.65; p = 0.02) was significantly associated with lower csPCa detection at TBx, after accounting for potential confounders. Conclusion: The presence of previous prostate surgery significantly decreases the accuracy of mpMRI in detecting csPCa. These results should be taken into account when assessing patients with a history of prostatic surgery and a suspicious lesion at mpMRI, to better select those who might avoid an unnecessary biopsy.